Enhancement of tumor‐associated antigen‐specific T cell responses by radiofrequency ablation of hepatocellular carcinoma12. Issue 4 (8th April 2013) - Mizukoshi, Eishiro; Yamashita, Tatsuya; Arai, Kuniaki; Sunagozaka, Hajime; Ueda, Teruyuki; Arihara, Fumitaka; Kagaya, Takashi; Yamashita, Taro; Fushimi, Kazumi; Kaneko, Shuichi
Abstract Radiofrequency ablation (RFA) is one of the treatments for hepatocellular carcinoma (HCC) and is known to enhance host immune response. However, the epitopes to which enhanced immune responses occur, the impact on patient prognosis, and the functions and phenotype of T cells induced are still unclear. To address these issues, we analyzed immune responses before and after RFA in 69 HCC patients using 11 tumor‐associated antigen (TAA)‐derived peptides that we identified to be appropriate to analyze HCC‐specific immune responses. The immune responses were analyzed using enzyme‐linked immunospot (ELISPOT) assay and tetramer assays using peripheral blood mononuclear cells. An increase in the number of TAA‐specific T cells detected by interferon‐γ ELISPOT assays occurred in 62.3% of patients after RFA. The antigens and their epitope to which enhanced T cell responses occur were diverse, and some of them were newly induced. The number of TAA‐specific T cells after RFA was associated with the prevention of HCC recurrence, and it was clarified to be predictive of HCC recurrence after RFA by univariate and multivariate analyses. The number of TAA‐specific T cells after RFA was inversely correlated with the frequency of CD14+HLA‐DR−/low myeloid‐derived suppressor cells (MDSCs). The modification of T cell phenotype was observed after RFA. The number of TAA‐specific T cells at 24 weeks after RFA was decreased. Conclusion: Although RFA can enhance various TAA‐specific T cell responses and the T cells induced contribute to the HCC recurrence‐free survival of patients, besides immunosuppression by MDSCs, the memory phenotype and lifetime of TAA‐specific T cells are not sufficient to prevent HCC recurrence completely. Additional treatments by vaccine or immunomodulatory drugs might be useful to improve the immunological effect of RFA. (Hepatology 2013;1448–1457)